Divergence of Desiccation-Related Traits in Sitobion avenae from Northwestern China - Yang, Yujing (Insects, 2020)
SIMPLE SUMMARY: Increasing frequency and intensity of drought has been causing increasing vulnerability for many ecosystems around the globe; thus, it is critical to understand how insects evolve in changing environments. We collected and genotyped samples of the wheat aphid Sitobion avenae from arid areas of northwestern China, and then examined their desiccation-related traits. We found both desiccation-resistant and -nonresistant genotypes, providing clear evidence of genetic divergence in desiccation resistance of this aphid. Wingless individuals tended to have higher desiccation resistance than winged ones. Extensive analyses of desiccation-related traits showed that modulation of water loss rates could be the primary mechanism underlying aphids’ resistance against desiccation stress. The content of cuticular hydrocarbons (especially methyl-branched alkanes) and their high plasticity could be closely linked to water loss rates in aphids, thereby modulating their desiccation resistance. This study can provide insights into how insects adapt to desiccating environments, and has particular relevance to the prediction of insect pest outbreaks under future warming scenarios. ABSTRACT: The impact of drought on insects has become increasingly evident in the context of global climate change, but the physiological mechanisms of aphids’ responses to desiccating environments are still not well understood. We sampled the wheat aphid Sitobion avenae (Fabricius) (Hemiptera: Aphididae) from arid areas of northwestern China. Both desiccation-resistant and -nonresistant genotypes were identified, providing direct evidence of genetic divergence in desiccation resistance of S. avenae. Resistant genotypes of wingless S. avenae showed longer survival time and LT50 under the desiccation stress (i.e., 10% relative humidity) than nonresistant genotypes, and wingless individuals tended to have higher desiccation resistance than winged ones. Both absolute and relative water contents did not differ between the two kinds of genotypes. Resistant genotypes had lower water loss rates than nonresistant genotypes for both winged and wingless individuals, suggesting that modulation of water loss rates could be the primary strategy in resistance of this aphid against desiccation stress. Contents of cuticular hydrocarbons (CHC) (especially methyl-branched alkanes) showed significant increase for both resistant and nonresistant genotypes after exposure to the desiccation stress for 24 h. Under desiccation stress, survival time was positively correlated with contents of methyl-branched alkanes for resistant genotypes. Thus, the content of methyl-branched alkanes and their high plasticity could be closely linked to water loss rate and desiccation resistance in S. avenae. Our results provide insights into fundamental aspects and underlying mechanisms of desiccation resistance in aphids, and have significant implications for the evolution of aphid populations in the context of global warming.